Clinical epidemiological, endoscopic and histologic aspects in elderly with esophagus cancer - Yurislena Monier Martínez; Anely Rosalia León Columbié; Jesús Díaz Fondén; Odalis Despaigne Guillot; Yoilán Rojas Columbié (Medisan, 2022)
Introduction: The esophagus cancer is one of the most invasive neoplasms and it means a less survival, because it is generally diagnosed in a late way, mainly in people over 60 years.